Cost-Effectiveness Analysis of Ibuprofen Versus Indomethacin or Paracetamol for the Treatment of Patent Ductus Arteriosus in Preterm Neonates - Samaher Al-Shaibi (14152206) (2023)
This was a first-time evaluation that sought to analyze the cost-effectiveness of oral paracetamol and intravenous (IV) indomethacin as alternatives to ibuprofen for PDA in neonates. Decision-analytic, literature-based, economic simulation models were constructed, to follow up the use and consequences of oral/IV ibuprofen versus IV indomethacin, and oral/IV ibuprofen versus oral paracetamol, as first-line therapies for PDA closure. Model outcomes of interest were “success”, defined as PDA closure with/without adverse events, or “failure” due to no response to the first course of treatment, death or premature discontinuation of therapy due to adverse events. Oral ibuprofen is dominant/cost-effective over IV indomethacin in 97.9% of simulated cases, but oral paracetamol was 75.2% dominant/cost-effective over oral ibuprofen. Against IV ibuprofen, IV indomethacin was 55.3% dominant/cost-effective, whereas oral paracetamol was dominant/cost-effective in 98.5% of the cases. Sensitivity analyses confirmed the robustness of the study results. For PDA closure, while IV indomethacin was cost-effective against IV ibuprofen, oral paracetamol was cost-effective against both oral and IV ibuprofen. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2023.101751